Michael Klim's Arm Actions at 70 m of His Butterfly Leg of the Gold Medal 4x100 m Men's Medley Relay at the 1998 Perth World Championships - Rushall, B. S. (1999)
Video pictures (12 frames) and the appropriate technical/ biomechanical explanations for Michael Klim's Arm Actions at 70 m of His Butterfly Leg of the Gold Medal 4x100 m Men's Medley Relay at the 1998 Perth World Championships.